2015
DOI: 10.1007/s00467-015-3188-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of vascular structure and function in pediatric hypertension

Abstract: Hypertension is associated with adverse cardiovascular (CV) events in adults. Measures of vascular structure and function including increased carotid intima-media thickness (cIMT) and elevated arterial stiffness predict hard CV events in adulthood. Newer data suggest abnormalities in target organ damage are occurring in adolescents and young adults with high blood pressure. In this review, we will discuss the techniques to measure vascular dysfunction in youth and the evidence linking blood pressure levels to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 86 publications
0
16
1
3
Order By: Relevance
“…Grade (eg, stroke, myocardial infarction, etc), 69 and FMD, which assesses endothelial function and describes the ability of the endothelium to release nitric oxide in response to stress. 375 Although there are multiple large studies of PWV in youth, 376 -381 they all suffer from notable limitations, primarily the lack of racial and ethnic diversity and differences in measurement devices and protocols. Researchers in the largest study of PWV in youth to date (N = 6576) only evaluated 10 and 11 year olds and measured only carotid-radial PWV across the arm; this measure has not been linked to CV events in adults.…”
Section: Aggregate Evidence Qualitymentioning
confidence: 99%
“…Grade (eg, stroke, myocardial infarction, etc), 69 and FMD, which assesses endothelial function and describes the ability of the endothelium to release nitric oxide in response to stress. 375 Although there are multiple large studies of PWV in youth, 376 -381 they all suffer from notable limitations, primarily the lack of racial and ethnic diversity and differences in measurement devices and protocols. Researchers in the largest study of PWV in youth to date (N = 6576) only evaluated 10 and 11 year olds and measured only carotid-radial PWV across the arm; this measure has not been linked to CV events in adults.…”
Section: Aggregate Evidence Qualitymentioning
confidence: 99%
“…Several mechanisms link obesity and high blood pressure, including upregulation of pro‐inflammatory adipokines due to adipose tissue dysfunction, increased sympathetic nervous system, abnormal kidney function associated with increased tubular sodium reabsorption, and increasing arterial stiffness 25‐31 . It has also been hypothesized that obesity‐related changes in the composition and function of gut microbiota might be associated with hypertension 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Results from our study suggest that the prevention of central obesity may play an important role in the prevention of hypertension in adolescents and young adults with type 1 or type 2 diabetes. This may prevent obesity‐related metabolic changes involved in the development of hypertension 25‐31 . However, previous analyses also showed that microvascular complications of diabetic kidney disease, retinopathy, and peripheral neuropathy were higher among youths and young adults with type 2 diabetes compared to those with type 1 even after adjustment for central obesity, glycemic control, and other factors over time 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Vasculatura: A pesar de que aún su uso no es rutinario, es importante considerar evaluación de la estructura y función vascular a través de pruebas no invasivas, ya que estudios han demostrado daño ateroesclerótico precoz en adolescentes hipertensos 1,11 . Estas pruebas incluyen: -Función endotelial: se mide la dilatación de la arteria braquial mediada por flujo.…”
Section: Fondo De Ojounclassified